Context Matters: How an Ecological-Belonging Intervention Can Reduce Inequities in STEM. (23rd February 2022) - Hammarlund, Sarah P; Scott, Cheryl; Binning, Kevin R; Cotner, Sehoya
Abstract: Doubts about belonging in the classroom are often shouldered disproportionately by students from historically marginalized groups, which can lead to underperformance. Ecological-belonging interventions use a classroom-based activity to instill norms that adversity is normal, temporary, and surmountable. Building on prior studies, we sought to identify the conditions under which such interventions are effective. In a chemistry course (study 1), students from underrepresented ethnic backgrounds underperformed relative to their peers in the absence of the intervention. This performance gap was eliminated by the intervention. In an introductory biology course (study 2), there were no large performance gaps in the absence of the intervention, and the intervention had no effect. Study 2 also explored the role of the instructor that delivers the intervention. The intervention boosted scores in the classrooms of instructors with a fixed (versus growth-oriented) intelligence mindset. Our results suggest that ecological-belonging interventions are more effective in more threatening classroom contexts.